∫ 0 π / 2 e x sin x cos x d x
If the above integral can be expressed as d a + e b π / c , where a , b , c and d are positive integers with b and c coprime, find the value of a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution... (+1)..
I like your approach.. (+1)
Log in to reply
Thanks to Euler, greatest mathematician of all times.
I didn't thought of de moivre's formula for sin2x, so I just proceed it with IBP. Hats off to you sir for The beautiful solution of yours.
Note that we have 3 distinct terms in the integrand. But it would be convenient to use IBP if we have two terms instead of 3. Hence , we rewrite the given integral as 2 1 ∫ 0 2 π e x sin 2 x d x using the identity sin 2 x = 2 sin x cos x . Now we conveniently evaluate this integral using Integration by parts:
u = sin ( 2 x ) ⇒ d u = 2 cos 2 x d x , d v = e x d x ⇒ v = e x , hence we have:
2 1 ∫ 0 2 π e x sin 2 x d x = 2 1 ( e x sin ( 2 x ) ∣ ∣ ∣ ∣ 0 2 π − 2 ∫ 0 2 π e x cos 2 x d x ) = 2 1 ( 0 − 2 ( e x cos ( 2 x ) ∣ ∣ ∣ ∣ 0 2 π + 2 ∫ 0 2 π e x sin 2 x d x ) ) The above step is by IBP ( u = cos 2 x , d v = e x d x ) ⇒ 2 I = 2 2 e π / 2 + 2 − 4 I w h e r e I = ∫ 0 2 π e x sin 2 x d x ⇒ 5 I = 2 ( e π / 2 + 1 ) ⇒ I = 5 2 ( e π / 2 + 1 ) ⇒ 2 I = 5 ( e π / 2 + 1 ) ⇒ ∫ 0 2 π e x sin x cos x d x = 5 ( e π / 2 + 1 )
Hence , a = 1 , b = 1 , c = 2 , d = 5 ⇒ a + b + c + d = 9 /
Good approach.
what is ibp?
Log in to reply
Log in to reply
lol i know what it is srry i just didnot know it was abbreviated ibp − −
Log in to reply
@Mardokay Mosazghi – Yeah,I figured that out :-)
Same way..
Problem Loading...
Note Loading...
Set Loading...
∫ 0 2 π e x sin x cos x d x = 2 1 ∫ 0 2 π e x sin ( 2 x ) d x = 4 i ∫ 0 2 π e x ( e − 2 x i − e 2 x i ) d x = 4 i ( ∫ 0 2 π e ( 1 − 2 i ) x d x − ∫ 0 2 π e ( 1 + 2 i ) x d x ) = 4 i ∫ 0 2 π ( e ( 1 − 2 i ) x − e ( 1 + 2 i ) x ) d x = 4 i [ 1 − 2 i e ( 1 − 2 i ) x − 1 + 2 i e ( 1 + 2 i ) x ] 0 2 π = 4 i [ 1 + 4 e x ( e − 2 x i − e 2 x i + 2 i e − 2 x i + 2 i e 2 x i ) ] 0 2 π = 2 × 5 i [ e x ( sin ( 2 x ) + 2 i cos ( 2 x ) ) ] 0 2 π = 1 0 i [ e 2 π ( sin π + 2 i cos π ) − e 0 ( sin 0 + 2 i cos 0 ) ] = 1 0 i [ − 2 i e 2 π − 2 i ] = 5 1 + e 2 π
⇒ a + b + c + d = 1 + 1 + 2 + 5 = 9